2022
DOI: 10.1021/acs.joc.2c02061
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light Organophotoredox-Mediated [3 + 2] Cycloaddition of Arylcyclopropylamine with Structurally Diverse Olefins for the Construction of Cyclopentylamines and Spiro[4.n] Skeletons

Abstract: We developed a visible-light-mediated [3 + 2] cycloaddition of arylcyclopropylamine with structurally diverse olefins using QXPT-NPh as a highly efficient organic photoredox catalyst. We first achieved the use of various alkyl-substituted alkenes in intermolecular [3 + 2] cycloadditions with cyclopropylamine. We also developed a general and efficient strategy for the construction of structurally diverse cyclopentane-based spiro[4.n] skeletons with 1,3-difunctional groups, which broadly exist in natural product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 86 publications
0
12
0
Order By: Relevance
“…Therefore, we continued to test other photocatalysts. Many photocatalysts including the organic ones developed in our laboratory 14,15 have been tested (see the ESI for details †) and we found that most of the photocatalysts could promote the reaction and QXPT-NPhCN…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Therefore, we continued to test other photocatalysts. Many photocatalysts including the organic ones developed in our laboratory 14,15 have been tested (see the ESI for details †) and we found that most of the photocatalysts could promote the reaction and QXPT-NPhCN…”
Section: Resultsmentioning
confidence: 96%
“…This experiment shows that the N–H of 1a is essential, which is similar to our previous report on arylcyclopropylamines. 14 Stern–Volmer quenching studies showed that 1a quenched the visible-light-excited QXPT-NPhCN . However, both olefins 2a and 4p hardly quenched QXPT-NPhCN .…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations